When you have a negative exponent, you move the base with the negative exponent to the other side of the fraction to make the exponent positive.
For example:
[tex]\frac{1}{2y^{-3}} =\frac{y^3}{2}[/tex] ("y" is the base with the negative exponent)
[tex]x^{-5}[/tex] or [tex]\frac{x^{-5}}{1} =\frac{1}{x^5}[/tex]
When you multiply an exponent directly to a base with an exponent, you multiply the exponents together.
For example:
[tex](y^3)^2=y^{(3*2)}=y^6[/tex]
[tex](x^2)^4=x^{(2*4)}=x^8[/tex]
[tex](2n)^3[/tex] or [tex](2^1n^1)^3=2^{(1*3)}n^{(1*3)}=2^3n^3=8n^3[/tex]
When you have an exponent of 0, the result will always equal 1
For example:
[tex]x^0=1[/tex]
[tex]5^0=1[/tex]
[tex]y^0=1[/tex]
[tex](6m^{-1}*n^0)^{-3}[/tex] I think you should first make the exponents positive
[tex]\frac{1}{(\frac{6}{m^1} *n^0)^3}[/tex]
Since you know:
m = 3
n = -5 Substitute/plug it into the equation
[tex]\frac{1}{(\frac{6}{(3)^1}*(-5)^0)^3 }[/tex]
[tex]\frac{1}{(2*1)^3}[/tex]
[tex]\frac{1}{2^3}[/tex]
[tex]\frac{1}{8}[/tex]